Modeling the Health and Budgetary Impacts of a Team-based Hypertension Care Intervention That Includes Pharmacists. Issue 11 (November 2019) - Overwyk, Katherine J.; Dehmer, Steven P.; Roy, Kakoli; Maciosek, Michael V.; Hong, Yuling; Baker-Goering, Madeleine M.; Loustalot, Fleetwood; Singleton, Christa-Marie; Ritchey, Matthew D.
Abstract : Objective: The objective of this study was to assess the potential health and budgetary impacts of implementing a pharmacist-involved team-based hypertension management model in the United States. Research Design: In 2017, we evaluated a pharmacist-involved team-based care intervention among 3 targeted groups using a microsimulation model designed to estimate cardiovascular event incidence and associated health care spending in a cross-section of individuals representative of the US population: implementing it among patients with: (1) newly diagnosed hypertension; (2) persistently (≥1 year) uncontrolled blood pressure (BP); or (3) treated, yet persistently uncontrolled BP—and report outcomes over 5 and 20 years. We describe the spending thresholds for each intervention strategy to achieve budget neutrality in 5 years from a payer's perspective. Results: Offering this intervention could prevent 22.9–36.8 million person-years of uncontrolled BP and 77, 200–230, 900 heart attacks and strokes in 5 years (83.8–174.8 million and 393, 200–922, 900 in 20 years, respectively). Health and economic benefits strongly favored groups 2 and 3. Assuming an intervention cost of $525 per enrollee, the intervention generates 5-year budgetary cost-savings only for Medicare among groups 2 and 3. To achieve budget neutrality in 5 years across all groups, intervention costs per person need to be around $35 for Medicaid, $180 for private insurance, and $335 for Medicare enrollees. Conclusions: Adopting a pharmacist-involved team-based hypertension model could substantially improve BP control and cardiovascular outcomes in the United States. Net cost-savings among groups 2 and 3 make a compelling case for Medicare, but favorable economics may also be possible for private insurers, particularly if innovations could moderately lower the cost of delivering an effective intervention. Abstract : Supplemental Digital Content is available in the text.